2018
DOI: 10.1002/hep.30077
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar Protein Sorting 33B Is a Tumor Suppressor in Hepatocarcinogenesis

Abstract: Polarity defects are frequently involved in liver diseases, such as chronic hepatitis and hepatocellular carcinoma (HCC). It was reported that vacuolar protein sorting 33B (Vps33b) plays critical roles in the maintenance of hepatocyte polarity; however, the functional roles and mechanisms of Vps33b in HCC occurrence and progression remain unknown. First of all, we showed that Vps33b is down-regulated in human and mouse liver cancer samples, and the low expression levels of Vps33b correlate with the poor progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…Physically, VPS33B colocalizes and interacts with VIPAR to form the VPS33B/VIPAR complex, interacting with endosome marker RAB11A and playing a vital role in the intracellular trafficking and the hepatocyte polarity maintenance (Golachowska, Hoekstra, & van IJzendoorn, ; Wakabayashi, Dutt, Lippincott‐Schwartz, & Arias, ; C. Wang et al, ). For VPS33B/VIPAR complex defect, aberrant location of canalicular membrane proteins of BSEP, MDR3, and CEA were observed in VPS33B / VIPAR deficient patients and Vps33b knockout mice (Ackermann et al, ; Bull et al, ; Hanley et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Physically, VPS33B colocalizes and interacts with VIPAR to form the VPS33B/VIPAR complex, interacting with endosome marker RAB11A and playing a vital role in the intracellular trafficking and the hepatocyte polarity maintenance (Golachowska, Hoekstra, & van IJzendoorn, ; Wakabayashi, Dutt, Lippincott‐Schwartz, & Arias, ; C. Wang et al, ). For VPS33B/VIPAR complex defect, aberrant location of canalicular membrane proteins of BSEP, MDR3, and CEA were observed in VPS33B / VIPAR deficient patients and Vps33b knockout mice (Ackermann et al, ; Bull et al, ; Hanley et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of Vps3 correlate with poor prognosis of human squamous carcinoma lung cancer (Bao et al, 2016). Single nucleotide polymorphisms in Vps41 strongly associate with hereditary melanoma (Ibarrola-Villava et al, 2015), and a recent study reported Vps33B as an important tumor suppressor in hepatocarcinogenesis (Wang et al, 2018). In D. melanogaster, mutations in Vps8 and Vps18 lead to the development of melanotic tumors, that is strongly pigmented tumors originating from immune cells (Lorincz et al, 2016).…”
Section: Cancermentioning
confidence: 99%
“…Although an increasing number of diagnostic and therapeutic strategies have been developed, the prognosis of HCC patients remains poor 3 . This is mainly due to the key genes and molecular mechanisms involved in HCC pathogenesis and development remaining largely unclear 3,4 .…”
Section: Introductionmentioning
confidence: 99%